Pelaksanaan Sensus Harian Rawat Inap di Rumah Sakit Elisabeth Medan - Agnes Jeane Zebua; Nayanda Privanezsa Hao (Yayasan Literasi Sains Indonesia, 2022)
Processing of the daily inpatient census starts from filling out the daily inpatient census by the head of the room or the person in charge and the daily inpatient census is sent to the medical record room every working day at 08.00 am. Information generated from daily inpatient census data in the form of inpatient management indicators consisting of BOR (Bed Occupancy Rate), TOI (Turn Over Interval), LOS (Length Of Stay), BTO (Bed Turn Over) to monitor activities in hospitalization and GDR (Gross Death Rate), NDR (Net Death Rate) to assess the quality of inpatient services. Implementation of the Daily Inpatient Census At Elisabeth Hospital Medan, it was found that the preparation of the daily inpatient census was guided by the technical instructions for filling out the daily inpatient census, but because the technical instructions in each ward were no longer available, there was no need to make the daily inpatient census. . Data collection methods used in this study were interviews and active participation observations using research instruments in the form of interview guidelines. The results showed that the standard procedure at RSE Medan in making the daily inpatient census had not been fully implemented when sending the daily inpatient census from the ward to the medical records department. The source of data in making the daily inpatient census is the inpatient service register book. The method of making a daily inpatient census at RSE Medan is not in accordance with the Ministry of Health of the Republic of Indonesia (2006).